Tie-Dye Batik Skills Training In Improving Entrepreneurial Creativity of SMK Uswatun Hasanah’s Students - Wahjusaputri, Sintha; Ernawati; Marlina, Elin; P., Sri Endang; Nastiti, Tashia Indah (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
This community activity program aims to provide counseling and practice of tie dye batik-making skills to foster students’ entrepreneurial spirit. This activity was carried out on July 8, 2021, at the Uswatun Hasanah Vocational School, Jakarta. Participants are teachers and students of class XII. The method of activities through counseling and practice uses an Active Learning approach of Small Group Work type with strict health protocols. The counseling and practice provided by the PKM Team to participants were to provide insight into tie-dye batik models and tie-dye batik making process starting from making patterns, color selection, coloring process, and drying tie-dye batik cloth. This community activity program for SMK students positively impacts growing motivation to create ideas, creativity, and tie-dye batik entrepreneurship.